Microtensile test in dental research. controversial aspects in statistical analysis (experimental unit and premature failures) - Daphne Camara Barcellos; Clovis Pagani; Mayra Cardoso; Ivan Balducci (Brazilian Dental Science)
Aims: The aim of this study was to present the controversial aspects in performing inferential statistical analysis with regard to selection of the experimental unit and procedures adopted in the case of pre-test failures.